Response of Rice Variety : Lakshmi(Kayamkulam-I) to different detes of Planting and Plant Density - Moni Perumal S (Department of Agronomy, College of Agriculture, 1989)
A study on Optimum time of planting of Lakshmi (Kayamkulam) variety of rice in relation to plant density with 18 treatment combinations in three replications in a split plot design was conducted in the instructional farm, Vellayani during mundakan season, 1985-1986. The main plot treatments were planting on 16th September, 1985 at ten days interval (T1,T2,T3,T4,T5 and T6). The three sub plot treatments were spacings of 20x 10 cm, 15x10 cm and 10x10 cm.(S1,S2 and S3 respectively). It was observed that planting during last week of September (26-9-1985) T2 and S2(15x10cm) spacing gave a marked influence on maximum productive tillers. The longer panicles were noticed in the normal date of planting (T1) while latest transplanting (T6) gave panicles of shortest length. Among the treatments 40 days after normal date of planting (26-10-1985) and 50 days after normal date of planting (5-11-1985) , (T5 and T6, respectively) and S2 spacing (15x10 cm) had a significant influence on larger number of spikelet’s,1000 grain weight and higher filled grains per panicle. Grain yields were highest in the treatments T5 (26-10-1985), T6 (05-11-1985) and s2 spacing (15x10cm) while higher straw yields were noticed in the early planted crops.